Factors That Influence On-Farm Decision-Making: Evidence from Weed Management. Issue 5 (4th May 2022) - Jussaume, Raymond A.; Dentzman, Katherine; Frisvold, George; Ervin, David; Owen, Micheal
Abstract: Scholars with an interest in agricultural social change have a long history of studying farmer decision-making. While much of the early research was focused on identifying the individual characteristics of progressive farmers, research has evolved into examinations of the many factors that may influence different types of farm decision-making, including the use of so-called Best Management Practices. We utilize an approach for analyzing farmer decision-making that includes some possible internal and external factors for understanding how farmers are responding to the emerging crisis of herbicide-resistant weeds. Based on survey data collected onfarm managers, we contrast farmers that are using an herbicide-centric approach with those who are adopting practices associated with integrated weed management. Our findings indicate that farm decision-making is a complex process that is influenced by a variety of factors.